Investigations of polyethylene glycol mediated ternary molecular inclusion complexes of silymarin with beta cyclodextrins - Mohammad Ansari (Journal of Applied Pharmaceutical Science, 2015)
Objective: To evaluate the effect of Polyethylene glycol and β-cyclodextrin on the solubility and dissolution of silymarin, a poorly water soluble herbal drug.Methodology: Effects of beta cyclodextrins and Polyethylene glycol on solubility of silymarin were evaluated by phase solubility studies both separately as well as in combination. Solid inclusion complexes of silymarin –β-cyclodextrin in 1:1 molar ratio were prepared with and without polyethylene glycol by kneading method then evaluated for solubility dissolution and physical nature by XRD, FT-IR and NMR spectroscopy studies.Results: The aqueous solubility of silymarin was linearly increased as a function of the concentration of β-cyclodextrin alone and in the presence of polyethylene glycol. Beta cyclodextrin formed molecular inclusion complexes with silymarin in1:1 molar ratio as revealed by phase solubility diagram. The ternary complexes of silymarin, β-cyclodextrin and polyethylene glycol demonstrated better dissolution than those of silymarin and its binary complexes with β-cyclodextrin alone. Silymarin - β-cyclodextrin complex caused 1.3 fold increase in the dissolution rate of silymarin, which was further increased up to 1.7 fold in presence of small amount of polyethylene glycol. Conclusion: The presence of polyethylene glycol markedly enhances the molecular complexation and solubilizing efficiencies of β-cyclodextrin on silymarin.
Keywords: Silymarin, Cyclodextrin, ternary complex, PEG 6000, Solubility, Dissolution rate.